FRI0246 Magnetic Resonance Imaging-Assessment of Early Response to Certolizumab Pegol in Rheumatoid Arthritis: A Randomized, Double-Blind, Placebo-Controlled Phase Iiib Study Applying Magnetic Resonance Imaging at Weeks 0, 1, 2, 4, 8 and 16. (10th June 2014) - Østergaard, M.; Jacobsson, L.; Schaufelberger, C.; Sejer-Hansen, M.; Bijlsma, J.; Dudek, A.; Rell-Bakalarska, M.; Staelens, F.; Haake, R.; Sundman-Engberg, B.; Bliddal, H.
Abstract : Background: The OMERACT rheumatoid arthritis (RA) magnetic resonance imaging (MRI) scoring system (RAMRIS) is a validated system for assessment of synovitis, bone edema and bone erosion. Previous studies have reported that anti-TNFs improve RAMRIS scores, but it is not known how early this occurs. The rapid clinical efficacy of certolizumab pegol (CZP), a PEGylated Fc-free anti-TNF, in RA has been reported. 1 Objectives: To identify the first time point of a MRI-verified response to CZP in RA patients (pts). Methods: MARVELOUS (NCT01235598 ) is a Phase IIIb multicenter, randomized, double-blind (DB), placebo (PBO)-controlled (during initial 2 weeks [wks]) study. Pts were randomized 2:1 to CZP Q2W (400mg at Wks 0–4, then 200mg every 2 wks to Wk16) or PBO at Day 0, then CZP Q2W (400mg Wks 2–6, then 200mg every 2 wks to Wk16). Contrast enhanced MRI of one hand and wrist was acquired at baseline (Wk0) and Wks 1, 2, 4, 8 and 16. Primary endpoint was change from Wk0 in OMERACT RAMRIS synovitis score in the CZP group. The first significance test was conducted at Wk16 and continued to earlier time points if significant. All MRIs were analyzed by an experienced reader blinded to subject identity, study treatment and time point; all time points were read simultaneously. Change in bone edema, bone erosion and clinical parameters were secondary outcomes. Last observation carried forward imputation was used for synovitis and observed data for other outcomes. Safety variables including adverse events (AEs) and laboratory parameters were assessed. Results: 40 pts were randomized and treated: CZP n=27; PBO–CZP n=13. During the DB phase, 4 pts discontinued treatment (1 PBO, 3 CZP). In the CZP group a significant reduction from baseline in synovitis score was reported at Wk16 (median change= -1.5, p=0.049; Fig. 1A ); reductions were not significant at Wk8, precluding testing of earlier time points. In the CZP group, bone edema score was also significantly reduced at Wk16 (-2.5, p=0.031; Fig. 1B ); there was no significant change in bone erosion score. For all RAMRIS parameters very good intra-reader reliability (intra-class correlations >0.90) was observed. Most AEs were mild or moderate with low incidence of withdrawal due to AEs. There were no serious infections or deaths. Conclusions: In this first study with multiple MRIs following initiation of biological therapy, CZP reduced OMERACT RAMRIS synovitis and bone edema scores as measured by MRI at Wk16, despite small sample size and the technical challenge of reading 6 time points simultaneously. This study documents the effect of CZP and provides essential information on the optimal timing of MRI and sample sizes for subsequent larger clinical trials. References: Keystone E. Arthritis Rheum 2008;58(11):3319-3329 Acknowledgements: The authors acknowledge Costello Medical Consulting for writing and editorial assistance which was funded by UCB Pharma. Disclosure of Interest: M. Østergaard Grant/research support: Abbott, Pfizer and Centocor, Consultant for: Abbott, Pfizer, Merck, Roche, UCB Pharma, Speakers bureau: Abbott, Pfizer, Merck, BMS, UCB Pharma, Mundipharma, L. Jacobsson Grant/research support: Pfizer, Paid instructor for: Abbvie, BMS, MSD, Pfizer, UCB Pharma, C. Schaufelberger: None declared, M. Sejer-Hansen Consultant for: UCB Pharma, J. Bijlsma Grant/research support: UCB Pharma, Speakers bureau: UCB Pharma, A. Dudek: None declared, M. Rell-Bakalarska: None declared, F. Staelens Employee of: UCB Pharma, R. Haake Employee of: UCB Pharma, B. Sundman-Engberg Employee of: UCB Pharma, H. Bliddal Grant/research support: Abbott, Amgen, AstraZeneca, Aventis, Axellus, Bristol Myers Squibb, Cambridge Nutritional Foods, Dansk Droge, Eurovita, Ferrosan, GlaxoSmithKline, Hoechst, LEO, Lundbeck, MSD, Mundipharma, Norpharma, NOVO, NutriCare, Nycomed, Pfizer, Pharmacia, Pierre-Fabre, Proctor&Gamble, Rhone-Poulenc, Roche, Roussel, Schering-Plough, Searle, Serono, UCB Pharma, Wyeth, Consultant for: Abbott, Amgen, AstraZeneca, Aventis, Axellus, Bristol Myers Squibb, Cambridge Nutritional Foods, Dansk Droge, Eurovita, Ferrosan, GlaxoSmithKline, Hoechst, LEO, Lundbeck, MSD, Mundipharma, Norpharma, NOVO, NutriCare, Nycomed, Pfizer, Pharmacia, Pierre-Fabre, Proctor&Gamble, Rhone-Poulenc, Roche, Roussel, Schering-Plough, Searle, Serono, UCB Pharma, Wyeth DOI: 10.1136/annrheumdis-2014-eular.2096